Building the Brand development Strategy of VNPT Technology period 2016-2020 and vision 2025 = Xây dựng chiến lược phát triển thương hiệu VNPT-Technology giai đoạn 2016-2020 và tầm nhìn 2025. - Dương, Đức Hạnh (2020)
In this thesis I would like to introduce VNPT Technology in the process of brand building and development, from which to draw practical lessons and suggest strategic solutions for branding, contributing a small part to the sustainable development of the industry. The thesis defining base on the theoretical framework of telecommunications products and services brand development to analysis VNPT Technology, explain the basic contents, that has implemented to build and develop telecommunication product and service brand, Point out the successes and limitations in VNPT Technology brand building and developing. From that thesis propose solutions to enhance the brand value of VNPT Technology.